Downregulation of Macrophage-Specific Act-1 Intensifies Periodontitis and Alveolar Bone Loss Possibly via TNF/NF-κB Signaling - Pathak, Janak L.; Fang, Ying; Chen, Yunxin; Ye, Zhitong; Guo, Xueqi; Yan, Yongyong; Zha, Jun; Liang, Dongliang; Ke, Xiuxian; Yang, Luxi; Zhong, Wenchao; Wang, Lijing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Periodontitis is a chronic inflammatory oral disease that affects almost half of the adult population. NF-κB activator 1 (Act1) is mainly expressed in immune cells, including macrophages, and modulates immune cells’ function to regulate inflammation in inflammatory diseases. Macrophages play a vital role in the pathophysiology of periodontitis. However, the effect of macrophage-specific Act1 on periodontitis has not been investigated yet. This study aims to unravel the role of macrophage-specific Act1 on the pathophysiology of periodontitis. The expression of Act1 in healthy and periodontitis periodontal tissue was confirmed by immunohistochemistry. Macrophage-specific Act1 expression downregulated (anti-Act1) mice were developed by inserting anti-Act1 antisense oligonucleotides after the CD68 promoter of C57BL/6 mice. Ligature-induced periodontitis (LIP) was induced in anti-Act1 mice and wildtype mice. Micro-CT, histology, and TRAP staining analyzed the periodontal tissue status, alveolar bone loss, and osteoclast numbers. Immunohistochemistry, RT-qPCR, and ELISA analyzed the inflammatory cells infiltration, expression of inflammatory cytokines, and M1/M2 macrophage polarization. mRNA sequencing of in vitro bacterial lipopolysaccharide (LPS)-treated peritoneal macrophages analyzed the differentially expressed genes in anti-Act1 mice during inflammation. Anti-Act1 mice showed aggravated periodontitis and alveolar bone loss compared to wildtype. Periodontitis-affected periodontal tissue (PAPT) of anti-Act1 mice showed a higher degree of macrophage infiltration, and M1 macrophage polarization compared to wildtype. Levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNFα), and macrophage activity-related factors (CCL2, CCL3, and CCL4) were robustly high in PAPT of anti-Act1 mice compared to wildtype. mRNA sequencing and KEGG analysis showed activated TNF/NF-κB signaling in LPS-treated macrophages from anti-Act1 mice. In vitro studies on LPS-treated peritoneal macrophages from anti-act1 mice showed a higher degree of cell migration and expression of inflammatory cytokines, macrophage activity-related factors, M1 macrophage-related factors, and TNF/NF-κB signaling related P-p65 protein. In conclusion, downregulation of macrophage-specific Act1 aggravated periodontitis, alveolar bone loss, macrophage infiltration, inflammation, and M1 macrophage polarization. Furthermore, LPS-treated macrophages from anti-Act1 mice activated TNF/NF-κB signaling. These results indicate the distinct role of macrophage-specific Act1 on the pathophysiology of periodontitis possibly via TNF/NF-κB signaling.